Studying the complexities in distributed object tracking systems - Llinas, J. (SMC'03 Conference Proceedings. 2003 IEEE International Conference on Systems, Man and Cybernetics. Conference Theme - System Security and Assurance (Cat. No.03CH37483), 2003)
Tracking of moving objects based on multisensor input is a topic that has received considerable attention, and has been the subject of many papers. As Web-type capabilities have emerged, along with ever-improving wireless communications capabilities, coupled with the needs of various applications to include "network-centric warfare" on the part of the military, research on distributed multi-object, multi-sensor tracking has received some attention in recent years. However, the study of these distributed problems at the complete-architecture level, accounting for (among yet other factors) organizational information-sharing protocols, dynamic network topologies, mixes of stationary and moving sensors, complex object dynamics, equipment failure modes, node-specific tracking algorithms and data fusion algorithms, does not seem to have been addressed in any "holistic" way. This paper addresses these issues and describes an integrated testbed being developed at the University at Buffalo's Center for Multisource Information Fusion for the empirical study of these complex architectures involving, in essence, the interconnection of multiple systems.